Richard Scarry's Smokey the fireman. - Scarry, Richard (Racine, Wis. : Western Pub. Co., 1988)
The adventures of a fire fighter at work and on his day off.
"A Golden book."
"A Golden easy reader"--Cover.
2.3
K-3
Keywords: Fire fighters -- Fiction; Animals -- Fiction; Cats -- Fiction; Fire fighters -- Fiction